Features of Spiritual Life in Uzbekistan - Kuyliyev Tulkin; Kenjayeva Dilrabo Rominovna (Miasto Przyszłości, 2023)
This article discusses the need for the people of our country, first of all, to strengthen in the hearts of young people a sense of belonging to the ongoing reforms, to further increase the effectiveness of spiritual and educational work in this area. In recent years, such important issues as the harmonious upbringing of the younger generation, the creation of all the necessary conditions for them to take an independent step in life, ensuring their rights and interests have become one of the priorities of state policy in the new Uzbekistan.